2022
DOI: 10.2967/jnumed.122.264041
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Outcomes of Cardiac Amyloidosis in All-Comer Referrals for Bone Scintigraphy

Abstract: The prevalence of cardiac amyloidosis (CA) in the general population and associated prognostic implications remain poorly understood. We aimed to identify CA prevalence and outcomes in bone scintigraphy referrals. Methods: Consecutive all-comers undergoing 99m Tc-3,3diphosphono-1,2-propanodicarboxylic-acid ( 99m Tc-DPD) bone scintigraphy between 2010 and 2020 were included. Perugini grade 1 was defined as low-grade uptake and grade 2 or 3 as confirmed CA. Allcause mortality, cardiovascular death, and heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
4
21
0
Order By: Relevance
“…In fact, AL CA can lead to significant myocardial tracer uptake and it is not possible to exclude AL with the use of scintigraphy [ 15 ]. In line with this, in another recent study by Nitsche and colleagues, up to 15% of biopsy-proven AL CA had a Perugini score ≥ 2 [ 16 ]. One patient in our cohort had AL CA without any evidence of monoclonal protein in the FLC assessment, as reported previously [ 17 ].…”
Section: Discussionsupporting
confidence: 63%
“…In fact, AL CA can lead to significant myocardial tracer uptake and it is not possible to exclude AL with the use of scintigraphy [ 15 ]. In line with this, in another recent study by Nitsche and colleagues, up to 15% of biopsy-proven AL CA had a Perugini score ≥ 2 [ 16 ]. One patient in our cohort had AL CA without any evidence of monoclonal protein in the FLC assessment, as reported previously [ 17 ].…”
Section: Discussionsupporting
confidence: 63%
“…These These results add to the emerging body of literature focusing on the pivotal role of cardiac valves in ATTR-CM. In patients with aortic stenosis, a significantly higher prevalence of concomitant ATTR 3,4 has been reported when compared to estimates for the general population, [5][6][7][8] whereas a potential contributing role of amyloid infiltration to the progression of stenosis severity remains controversial. Moreover, mitral regurgitation (MR) due to structural changes described above is a frequent finding in ATTR-CM as highlighted by data from the present study, where around two thirds of patients were affected by at least mild MR at baseline.…”
Section: This Article Refers To 'Progression Of Echocardiographic Par...mentioning
confidence: 99%
“…This highlights the utmost importance of additional single positron emission computed tomography (SPECT) in case of any cardiac uptake to confirm a myocardial tracer origin (as opposed to blood pool, ribs, or sternum). Nevertheless, even if we take into consideration patients with low‐grade cardiac uptake, there remains a large gap between prevalence estimates in elderly patients from bone scintigraphy on the one hand 3,4 and autopsy studies on the other hand 5,6 . One possible explanation may be a high prevalence of ‘subclinical’ amyloid deposits in the elderly, which are not accessible to current imaging techniques.…”
Section: Figurementioning
confidence: 99%
“…Comparable studies reported an ATTR prevalence of 1-3% in individuals ≥80 years old. 3,4 Moreover, the prevalence of 'early' ATTR infiltration, as indicated by low-grade cardiac tracer uptake, accounted for an additional ∼3% in these elderly patients. 3 However, we have to keep in mind the lower diagnostic accuracy of planar bone scintigraphy for a correct CA diagnosis in a low-risk population compared to patients with a high pre-test probability (e.g.…”
mentioning
confidence: 99%